An Analysis of Grammar Proficiency among Early-Level Learners of English Education Program at UIN Raden Mas Said Surakarta Using Statistical Methods - Indah Eftanastarini; Novianni Anggraini (CV. Creative Tugu Pena, 2026)
The purpose of this study was to analyze the level of grammatical understanding, to identify common grammatical errors made by learners of the English Language Education Study Program at the UIN Raden Mas Said Surakarta at early-level, as seen from statistical analysis, and to examine the factors influencing learners’ grammatical errors. This study used mix method to analyze the data. The sample of the study was 72 learners of English Education Program, Faculty of Adab and Language, UIN Raden Mas Said Surakarta. The results showed that the level of grammar understanding at early-level learners of English Education Program at UIN Raden Mas Said Surakarta was sufficient level. From the analysis results it was found that learners often made errors in the adjective component (2.93), adverb (2.90), and action adverb (2.79). There are four factors that influence grammar mastery, namely motivation, learning strategies and study habits, lecturers’ teaching methods, and learning environment and academic support.